2019
DOI: 10.3390/ijerph16203798
|View full text |Cite
|
Sign up to set email alerts
|

Neighborhood Deprivation and Risks of Autoimmune Disorders: A National Cohort Study in Sweden

Abstract: Background: No study to date, as far as we know, has analyzed the potential effect of neighborhood-level deprivation on autoimmune disorders (ADs), when adjusted for individual-level characteristics. Methods: A total of 5.4 million individuals from 8363 neighborhoods, comprising the whole Swedish population (ages 25–74 years), were followed for the period 1 January 2000, until admission due to diagnosis of ADs during the period of the study, or the conclusion of the study (31 December 2010). We used a neighbor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 35 publications
1
9
0
2
Order By: Relevance
“…These proinflammatory chemokines are involved in inflammation and response to infection and have been implicated in a variety of diseases including autoimmune, inflammatory, infectious as well as in cancer 38 . It is well-known that those living in poverty have higher rates of chronic infections such as cytomegalovirus (CMV) infection 42 and autoimmune diseases 43 . In agreement with this finding, IL-12B also plays an important role in sustaining immune responses against pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…These proinflammatory chemokines are involved in inflammation and response to infection and have been implicated in a variety of diseases including autoimmune, inflammatory, infectious as well as in cancer 38 . It is well-known that those living in poverty have higher rates of chronic infections such as cytomegalovirus (CMV) infection 42 and autoimmune diseases 43 . In agreement with this finding, IL-12B also plays an important role in sustaining immune responses against pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…A study from Sweden found that the level of deprivation in counties could affect the presence of psoriasis. 26 Especially in the region of north-eastern Germany, several deprived areas exist. For other chronic diseases, such as diabetes or obesity, it has been shown that prevalence rates are higher here 27 28 and that the overall morbidity is worse.…”
Section: Discussionmentioning
confidence: 99%
“…In the full model, where individual level characteristics were taken into account, the odds of ADs were 1.18 (1.14–1.22) in the most deprived neighborhoods. Certain ADs- … Crohn's disease (1.21) ... -remained significantly associated with high level of neighborhood deprivation after adjustment for the individual-level variables.” [ 186 ]…”
Section: Commonality Of Contributing Factors Between Ibd and Id - Detailsmentioning
confidence: 99%